PENGEMBANGAN LANDING PAGE EDUKATIF BERBASIS PROYEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) SUARA DEMOKRASI DI SMP BINA SEJAHTERA SUKMAJAYA DEPOK - Romdoni, Aceng; Abduh, Mohamad; Rumiati, Sri (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
This study aims to develop an Educational Landing Page media based on the Pancasila Student Profile Strengthening Project (P5) with the theme Voice of Democracy as a learning tool that can improve the leadership and justice character of junior high school students. This study uses the Research and Development (R&D) method with the Borg and Gall development model. The research subjects were eighth grade students of Bina Sejahtera Junior High School involving two classes, namely the experimental class and the control class. Data collection instruments included expert validation questionnaires, observations, reflective notes, and character tests before and after media use (pretest-posttest). The feasibility test was carried out by material, media, and communication experts, which showed that this media fell into the category of